Production of Sugar From Sweet Sorghum Stems with Hydrolysis Method Using Trichoderma viride - Ndapamuri, Melycorianda Hubi; Herawati, Maria Marina; Meitiniarti, V Irene (Biosaintifika: Journal of Biology & Biology Education, 2021)
Sorghum stem bagasse waste is one of the materials with high cellulose content. It can be utilized in glucose production through enzymatic hydrolysis of cellulose by Trichoderma viride. This study aims to determine sorghum stem bagasseâ€™s potential in producing glucose, assessing the time and concentration of sorghum stem bagasse in the hydrolysis process to produce glucose optimally and following SNI. Hydrolysis was carried out using a concentration of 5%, 8%, and 11% sorghum stem bagasse for 10, 15, and 20 days. The results showed that sorghum stem bagasse waste could produce glucose with an average glucose yield of 10.09% to 24.40 %. There is a tendency that increasing substrate concentration and hydrolysis time will increase the yield of liquid glucose. The treatment of 5% concentration of sorghum stem bagasse with a long hydrolysis time of 10 days can produce the highest liquid glucose, namely 24.40% with total dissolved solids of 7.40% Brix, the ash content of 0.26%, but 47.54% water content has not met SNI standards.Â